Health seeking behaviour of the mothers for illness of their under five children in slums of Dibrugarh town, Assam, India - Borah, Hiyeswar; Gogoi, Gourangie; Saikia, Hiranya (International Journal Of Community Medicine And Public Health, 2017)
Background: The under- five mortality continues to rise globally at an annual rate of 24% despite efforts to counteract it through vertical programmes. In Indian slums nearly 100,000 babies die every year before their fifth birthday. Apart from poor nutrition and environmental conditions, poor health-seeking behaviour contributes to the high child morbidity and mortality among the urban poor. Aim of the study is to assess the health seeking behaviour of the mothers for illness of their under-five children. Methods:A community based cross-sectional study was carried out in slums of Dibrugarh town, Assam, India. The sample size was allocated proportionally among the slums. The data was collected in a pre-designed pre-tested proforma after taking informed consent. Percentages were calculated and also Chi square test and Fisher’s exact test were performed to test the associations. Results: Total 416 under five children were included in the study, out of which 50.7% were male and 49.3% were female. 70.2% had suffered from atleast one morbidity of which 41.8% consulted with government doctor, private doctors 9.6%, health workers 17.5%, and elderly family member 16.8%, whereas 32.5% were not doing anything during the illness. The health advice seeking was low among illiterate mothers. There was a significant association between literacy status and health seeking behaviour (p < 0.05). Ignorance was the commonest reason for not seeking health advice. Conclusions:There is a need to raise awareness regarding health of under-five children by increasing the literacy status of mothers among slum dwellers to improve the health seeking behaviour.